Successfully Introducing the Methods and Instruments for Flexible Business Processes Automation into Romanian Companies - Paul BRUDARU; Ionel NĂFTĂNĂILĂ (Revista de Management Comparat International)
An approach containing methods and instruments adapted to the economical environment conditions with a high speed changing rate would be the synthetic description of the BPM (Business Process Management). This approach was absorbing instruments from both business management and information technology field, being situated at the border between the interests of two scientific communities, therefore revealing a high degree of modernity and innovation.